PARENTS' PERSPECTIVES ON THE ADAPTATION OF THE FIRST GRADE CHILDREN AFTER THE COVID-19 PANDEMIC: TRANSITION FROM KINDERGARTEN TO FIRST GRADE ELEMENTARY SCHOOL - Annisa Nur Wahyuningsih; Nurbiana Dhieni; Elindra Yetti (International Conferences on Early Childhood Education Proceedings, 2023)
One of the impacts of the COVID-19 pandemic in education is the adaptation of children in the transition period to enter first grade elementary school, because the transition from kindergarten to first grade elementary school is a major change in children's dailyroutine life. One of the supporting factors in the success of children's school adaptation is the relationship between parents and children and the relationship between parents and schools. The purpose of this study was to explore parents' perspectives on the adaptation of first grade students during the transition from kindergarten to first grade. This study used qualitative research methods, with phenomenological design. The study conducted interviews with 3 parents who had children in first gradeof elementary school. Analysis uses interviews and documentation to analyze research findings. The results showed that the topics identified to parents of first grade elementary school children were efforts made by parents to prepare children to enter first grade elementary school after the COVID-19 pandemic; adaptation indicators considered by the child's parents at the beginning of the first year of primary school; and the relationship between teachers and parents in the adaptation process of first gradeelementary school children.